CITRA PEREMPUAN TOKOH UTAMA DALAM NOVEL PEREMPUAN BAYANGAN KARYA NETTY VIRGIANTINI KAJIAN SASTRA FEMINIS - Wantry Simanungkalit; Dardanila; Emma Marsella (Jurnal Bastra (Bahasa dan Sastra), 2025)
Literature is a representation of life’s realities conveyed through the imagination of the author. As one form of literary work, the novel not only presents a narrative but also reflects perspectives on social conditions, including the image of women. This study aims to examine the image of women in the novel Perempuan Bayangan by Netty Vergiantini, focusing on the main character, Ningrum. The study employs feminist literary theory and a qualitative descriptive method to analyze the data. The analysis centers on three main aspects of the female image: physical, psychological, and social. (1) The physical image includes descriptions of the character’s body and appearance. (2) The psychological image reflects the character’s mental state, emotions, and way of thinking. (3) Meanwhile, the social image is seen through the character’s position in society and her relationship with the surrounding environment. The results show that these three aspects are interconnected in shaping the portrayal of the female image in the novel. This study is expected to contribute to feminist literary studies and serve as a reference for future research on the representation of women in literary works. Keywords: novel, feminist literature, female image, main character.